Individualization and interdisciplinarity in Physical Education teaching at higher education institutions - Gošnik, Jelka (Array, 2010)
In this paper, the individualization of teaching is observed in kinesiological education at higher education institutions which is with its organization and programs closely linked to the kinesiological education in primary and secondary schools. It also emphasizes the need for understanding of individualization in the context of achieving the educational practice that is coordinated with the students' biopsychosocial characteristics and their nature of experience and understanding themselves and world around them, as well as their own ways of learning kinesiological contents. At the same time it is put emphasis on a new modern approach to kinesiological education and a subject in teaching which has characteristics of an open system that is liable to continuous development as a result of all changes in personal paradigm of the subject. Based on the data from researches performed in the last few years at Faculty of Humanities and Social Sciences, at Faculty of Science and at Polytechnic of Zagreb, there is a need for interdisciplinary approach to individualized teaching kinesiological contents at higher education institutions. The paper presents an interdisciplinary course Man and sport as a result of appreciation of all individual characteristics, attitudes and preferences of freshmen, as well as their health predispositions that are necessary for successful achievement of the objectives of Physical Education teaching. This course with its diverse contents from various sciences and disciplines provides the individualization of kinesiological education at Faculty of Humanities and Social Sciences in Zagreb and indicates the importance of interdisciplinary approach to kinesiological education and sport.